Performing Identity and Concealment: Kim Mo-Mi’s Shifting Selves and the Illusion of Freedom in Mask Girl - Saranietha Kadang; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study explores the shifting identities of Kim Mo-Mi in the South Korean psychological thriller Mask Girl, focusing on how the protagonist uses literal and symbolic masks to navigate societal beauty standards and reclaim agency. Drawing on Erving Goffman's dramaturgical theory and Anthony Giddens’ agency theory, this research analyzes the meanings behind the masks Mo-Mi wears across three life stages—online performer, surgically altered persona, and prisoner—and investigates the reasons she chooses to keep them. Using close textual and visual analysis, the study finds that Mo-Mi’s masks serve distinct functions: performance, transformation, and survival. The findings reveal that while each mask appears to offer her empowerment or escape, they ultimately reflect the constraints imposed by societal structures and her struggle to assert her identity. The study concludes that the mask, rather than merely concealing appearance, becomes both a tool of agency and a symbol of entrapment within social expectations. In the end, the story shows that real freedom comes not from wearing a mask, but from having the courage to live as her true self without hiding.